Data ethics in the age of AI - Khan, Arshad (MLI generative AI series, 2025)
In a world increasingly shaped by data and artificial intelligence, the ethical challenges surrounding data use have never been more critical. Data Ethics in the Age of AI provides a compelling exploration of the moral, legal, and societal dimensions of data in the digital era.This insightful book delves into key issues such as privacy, algorithmic bias, transparency, and accountability, offering readers a robust framework for navigating the complex intersection of technology and ethics. With real-world examples and thought-provoking discussions, it equips business leaders, policymakers, researchers, and students with the knowledge and tools to foster ethical responsibility in the face of rapid technological advancements.Discover how we can build a future where data is used responsibly, equitably, and for the greater good. Data Ethics in the Age of AI is your essential guide to understanding and shaping the ethical landscape of our data-driven world